Prdm12 Directs Nociceptive Sensory Neuron Development by Regulating the Expression of the NGF Receptor TrkA - Simon Desiderio; Simon Vermeiren; Claude Van Campenhout; Sadia Kricha; Elisa Malki; Sven Richts; Emily V. Fletcher; Thomas Vanwelden; Bela Z. Schmidt; Kristine A. Henningfeld; Tomas Pieler; C. Geoffrey Woods; et al. (Cell Reports, 2019)
Summary: In humans, many cases of congenital insensitivity to pain (CIP) are caused by mutations of components of the NGF/TrkA signaling pathway, which is required for survival and specification of nociceptors and plays a major role in pain processing. Mutations in PRDM12 have been identified in CIP patients that indicate a putative role for this transcriptional regulator in pain sensing. Here, we show that Prdm12 expression is restricted to developing and adult nociceptors and that its genetic ablation compromises their viability and maturation. Mechanistically, we find that Prdm12 is required for the initiation and maintenance of the expression of TrkA by acting as a modulator of Neurogenin1/2 transcription factor activity, in frogs, mice, and humans. Altogether, our results identify Prdm12 as an evolutionarily conserved key regulator of nociceptor specification and as an actionable target for new pain therapeutics. : Desiderio et al. report that, in developing somatosensory neurons, Prdm12 is restricted to the nociceptors and that these are selectively eliminated from Prdm12 mutant mice. In Xenopus and human iPSCs, they show that Prdm12, in conjunction with bHLH proneural proteins, promotes the expression of the neurotrophin receptor TrkA. Keywords: zinc-finger transcription factor, neurotrophic receptor, nociceptors, pain, cell fate specification, mouse, Xenopus, stem cells